2018
DOI: 10.3892/or.2018.6510
|View full text |Cite
|
Sign up to set email alerts
|

LC‑MS/MS metabolome analysis detects the changes in the lipid metabolic profiles of dMMR and pMMR cells

Abstract: The DNA mismatch repair (MMR) system plays an important role in the initiation, diagnosis and treatments of colorectal cancer (CRC). Compared to CRC patients deficient in DNA MMR (dMMR), CRC patients proficient in DNA MMR (pMMR) have higher metastasis, short survival and poor response to chemotherapy and immunotherapy. It is well‑known that a high‑fat diet can cause CRC, and lipid metabolism is closely related to the development and metastasis of CRC. However, there have been few studies that address the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
3
12
0
2
Order By: Relevance
“…The SW620 cells, isolated from distant metastatic tissue, showed a largely distinct pattern of SL ratios, being more similar to normal or to adenoma cells (Figure 2A). This seems to correspond to the previously published observation that, in terms of LacCer or GluCer levels, they are closer to NCM460 cells [69].…”
Section: Lipidomic Analyses Of Human In Vitro Models Of Colon Cancsupporting
confidence: 92%
See 1 more Smart Citation
“…The SW620 cells, isolated from distant metastatic tissue, showed a largely distinct pattern of SL ratios, being more similar to normal or to adenoma cells (Figure 2A). This seems to correspond to the previously published observation that, in terms of LacCer or GluCer levels, they are closer to NCM460 cells [69].…”
Section: Lipidomic Analyses Of Human In Vitro Models Of Colon Cancsupporting
confidence: 92%
“…Just recently, some specific SL metabolism alterations were observed in a series of colon cancer cell lines [69]. Here, surprisingly, the authors have found that SL content was very similar in NCM460 cells, derived from normal colon mucosa, and in SW620 cells, isolated originally from lymph node metastasis of colon carcinoma.…”
Section: Lipidomic Analyses Of Human In Vitro Models Of Colon Cancmentioning
confidence: 78%
“…PLD hydrolyzes phosphatidylcholine producing phosphatidic acid, and there are two main isoforms: PLD1 and PLD2. PLD1, the key enzyme involved in lipid metabolism, is associated with metastasis [ 62 ]. PLD1 knockout mice resulted in mitochondrial abnormalities and subsequent lipid accumulation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (52) and Qian et al (53) observed that the invasive ability of A549 human lung adenocarcinoma and MCF-7 breast cells decreases following treatment with SMG after 72 h. A previous study reported that PS is associated with invasion of colorectal cancer cells (54). In the present study, it was demonstrated that PS [DiMe (11,3)/MonoMe (11,5)], PS [18:3 (9Z,12Z,15Z)/22:1(13Z)] and PS [14:1 (9Z)/24:0)] significantly decreased, suggesting that the the invasive ability of HGC-27 cells was weakened under SMG.…”
Section: Discussionmentioning
confidence: 97%